Heavy metals and trace elements in muscle of Silverside (Odontesthes bonariensis) and water from different environments (Argentina): Aquatic pollution and consumption effect approach - Avigliano, Esteban (2015)
The concentrations of As, Ag, B, Ba, Bi, Ca, Cd, Co, Cr, Fe, Ga, Hg, K, Li, Mg, Mn, Mo, Na, Ni, Pb, Rb, Sb, Se, Sn, Sr, Te, Ti, U, V and Zn were determined in water and silverside (Odontesthes bonariensis) muscle samples from four important commercial fishing sites (Argentina) by ICPMS. Trace element concentrations in water with well-documented human health effects were above the recommended maximum levels established by Argentinean and international guidelines for the aquatic biota protection in three sampling sites (e.g. As: 28.4-367 ìg L-1; Cd: 0.17-1.05 ìg L-144 ; Hg: 0.07-0.63 ìg L-1; Zn: 71.3-90.0 ìg L-145 ). High concentrations of As, Hg and Pb (0.03-0.76; 0.03-0.42 and 0.04-0.19 mg kg-1 wet weight, respectively) were found in silverside muscle. Fishing communities associated with contaminated environments are likely to have higher consumption rates and are thus more likely to be exposed to higher concentrations of the toxic elements (As, Hg and Pb).